Ação rescisória, Súmula 343 do STF e segurança jurídica - Barbosa, Juliana Guimarães (2016)
This article deals with the rescission action and its implications with regard to legal certainty in the light of understanding of changes in the high courts over time and the impact that such changes bring the claimants and citizens for the purpose of predictability of conduct. The discussion came up from recent positioning of the Supreme Court on the scope of Precedent 343 and new hypotheses of the appropriateness of termination under the new CPC on the grounds of unconstitutionality claims perpetrated by the Supreme Court. It studies how to reconcile the supremacy of the Constitution, equality and safety at the scene of intense jurisprudential changes that marks today's Brazilian Law.